2022
DOI: 10.1002/adma.202209495
|View full text |Cite
|
Sign up to set email alerts
|

Inverted and Amplified CP‐EL Behavior Promoted by AIE‐Active Chiral Co‐Assembled Helical Nanofibers

Abstract: Scheme 1. a) Structures of L/D-HP and NTi; b) Schematic diagram of the possible initial chiral co-assembly route of L-HP-NTi; c) Schematic diagram of the possible helical chiral co-assembly route of L-HP-NTi; d) Device configuration of the CP-OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 56 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…We found that the S-PB2, PTZ@S-PB2, and S-PT films had similar microstructures: from spherical aggregates (Figures 6a-d and S22a, b) to highly-ordered helical nanofibers (Figures 6e-h and S22c, d) which were formed during thermal anneal treatment, resulting in the reversed and amplified CPL emissions. [27] Compared with the SEM images of S-PT, PTZ@S-PB2 had more stereoregular spherical aggregates. Notably, spherical aggregates were found in annealed S-PT, which might reduce its negative CPL signals (Figure 6g and 6h).…”
Section: Resultsmentioning
confidence: 91%
“…We found that the S-PB2, PTZ@S-PB2, and S-PT films had similar microstructures: from spherical aggregates (Figures 6a-d and S22a, b) to highly-ordered helical nanofibers (Figures 6e-h and S22c, d) which were formed during thermal anneal treatment, resulting in the reversed and amplified CPL emissions. [27] Compared with the SEM images of S-PT, PTZ@S-PB2 had more stereoregular spherical aggregates. Notably, spherical aggregates were found in annealed S-PT, which might reduce its negative CPL signals (Figure 6g and 6h).…”
Section: Resultsmentioning
confidence: 91%
“…Before thermal annealing (panels a and b of Figure ), both R / S -3–LC-P and R / S -6–LC-P exhibit a weak induced CD band of LC-P in the chiral inducer weight percent range of 2.5–25%. Interestingly, the induced CD bands of these chiral co-assemblies can be greatly enhanced after being annealed at 150 °C, suggesting that suitable thermal annealing treatment can promote higher order orientation of chiral co-assemblies . The strongest mirror-image-induced CD signals can be observed from ( R / S -3) 0.05 –(LC-P) 0.95 and ( R / S -6) 0.1 –(LC-P) 0.9 when the weight-doping ratios of R / S -3 and R / S -6 are 5 and 10 wt %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the induced CD bands of these chiral co-assemblies can be greatly enhanced after being annealed at 150 °C, suggesting that suitable thermal annealing treatment can promote higher order orientation of chiral co-assemblies. 50 The strongest mirror-image-induced CD signals can be observed from (R/S-3) 0.05 −(LC-P) 0.95 and (R/S-6) 0.1 −(LC-P) 0.9 when the weightdoping ratios of R/S-3 and R/S-6 are 5 and 10 wt %, respectively. It is worth noting that the induced CD signal of (R/S-3) 0.05 −(LC-P) 0.95 is much higher than that of (R/S-6) 0.1 −(LC-P) 0.9 , which indicates that a more efficient intermolecular chiral induction can occur from chiral inducer R/S-3 to achiral LC-P during the chiral co-assembly process (panels e and f of Figure 2).…”
Section: ■ Experimental Sectionmentioning
confidence: 95%
“…The conventional approach for fabricating circularly polarized OLEDs mainly focuses on the design and synthesis of efficient organic materials with circularly polarized luminescence, which are subsequently utilized as the emitting centers in light-emitting layers (EMLs) [10][11][12] . Alternatively, circularly polarized OLEDs can also be obtained based on chirality-induction strategy of blending a chirality inducer with emitting materials during the preparation of the EMLs [13][14][15] . Essentially, the chiral nature of these devices originates from the chiral emitting materials or the chiral environments in EMLs [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%